Noninvasive treatment of breast cancer using high-intensity focused ultrasound - Zhou, Yufeng (2014)
Breast conserving surgery is a standard procedure for breast cancer since 1970. Now noninvasive therapy with few complications is preferred. High-intensity focused ultrasound (HIFU) has been developed to ablate solid tumor or cancer noninvasively. Its clinical outcome on breast cancer in China and Europe as well as the induced vascular destruction and immune response are summarized. In summary, HIFU is a promising therapeutic modality for breast cancer.